2014
DOI: 10.1088/0004-637x/792/2/87
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Profiles From Spinning Neutron Stars in the Hartle-Thorne Approximation

Abstract: We present a new numerical algorithm for the calculation of pulse profiles from spinning neutron stars in the Hartle-Thorne approximation. Our approach allows us to formally take into account the effects of Doppler shifts and aberration, of frame dragging, as well as of the oblateness of the stellar surface and of its quadrupole moment. We confirm an earlier result that neglecting the oblateness of the neutron-star surface leads to 5%-30% errors in the calculated profiles and further show that neglecting the q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 35 publications
1
60
0
Order By: Relevance
“…For example, there have been calculations of the light curve that are taking into account the Doppler factor and the time delay in the Schwarzschild spacetime [26,[29][30][31]. In other cases, light curves were calculated either within the Hartle-Thorne approximation [32] or in the numerically determined spacetime of rapidly-rotating neutron stars [33,34]. These works showed that the inclusion of effects such as Doppler, aberration and gravitational time-delay in the Schwarzschild spacetime can estimate relatively well the light curve produced by moderately rapidly-rotating neutron stars with spin frequencies 300 Hz, above which stellar oblateness becomes important [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…For example, there have been calculations of the light curve that are taking into account the Doppler factor and the time delay in the Schwarzschild spacetime [26,[29][30][31]. In other cases, light curves were calculated either within the Hartle-Thorne approximation [32] or in the numerically determined spacetime of rapidly-rotating neutron stars [33,34]. These works showed that the inclusion of effects such as Doppler, aberration and gravitational time-delay in the Schwarzschild spacetime can estimate relatively well the light curve produced by moderately rapidly-rotating neutron stars with spin frequencies 300 Hz, above which stellar oblateness becomes important [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…These effects have been shown to be small (in general relativity) and we expect them to be equally small in scalar-tensor gravity [81]. At high rotation frequencies (ν 300 Hz), the pulse profile is mostly affected by the quadrupolar deformation of the star [82][83][84][85][86][87] which, however, we do not include. However, we do include special relativistic effects of Doppler boost and aberration due to the rapid motion of the hot spot.…”
Section: A Assumptions and Model Parametersmentioning
confidence: 95%
“…Pulse Profile Modeling (also known as waveform or lightcurve modeling) exploits the effects of General and Special Relativity on rotationally-modulated emission from neutron star surface hot spots (see Figures 4 and 5 of [20] for examples that illustrate these effects). A body of work extending over the last few decades has established how to model the relevant aspects -which include gravitational light-bending, Doppler boosting, aberration, time delays and the effects of rotationally-induced stellar oblateness -with a very high degree of accuracy [21,22,23,24,25,26,27,28,29,30]. Given a model for the surface emission (surface temperature pattern, atmospheric beaming function, observer inclination) we can thus predict the observed pulse profile (counts per rotationalphase bin per energy channel) for a given exterior neutron star space-time (set by mass, radius and spin frequency -see the review by [16] for a more extended introduction to Pulse Profile Modeling).…”
Section: Pulse Profile Modelingmentioning
confidence: 99%